Infection Sources of a Common Non-tuberculous Mycobacterial Pathogen, Mycobacterium avium Complex - Nishiuchi, Yukiko; Iwamoto, Tomotada; Maruyama, Fumito (Frontiers in Medicine, 2017)
Numerous studies have revealed a continuous increase in the worldwide incidence and prevalence of nontuberculous mycobacteria (NTM) diseases, especially pulmonary Mycobacterium avium complex (MAC) diseases. Although it is not clear why NTM diseases have been increasing, one possibility is an increase of mycobacterial infection sources in the environment. Thus, in this review, we focused on the infection sources of pathogenic NTM, especially MAC. The environmental niches for MAC include water, soil, and dust. The formation of aerosols containing NTM arising from shower water, soil, and pool water implies that these niches can be infection sources. Furthermore, genotyping has shown that clinical isolates are identical to environmental ones from household tap water, bathrooms, potting soil, and garden soil. Therefore, to prevent and treat MAC diseases it is essential to identify the infection sources for these organisms, because patients with these diseases often suffer from reinfections and recurrent infections with them. In the environmental sources, MAC and other NTM organisms can form biofilms, survive within amoebae, and exist in a free-living state. Mycobacterial communities are also likely to occur in these infection sources in households. Water distribution systems are a transmission route from natural water reservoirs to household tap water. Other infection sources include areas with frequent human contact, such as soil and bathrooms, indicating that individuals may carry NTM organisms that concomitantly attach to their household belongings. To explore the mechanisms associated with the global spread of infection and MAC transmission routes, an epidemiological population-wide genotyping survey would be very useful. A good example of the power of genotyping comes from M. avium subsp. hominissuis, where close genetic relatedness was found between isolates of it from European patients and pigs in Japan and Europe, implying global transmission of this bacterium. It is anticipated that whole genome sequencing technologies will improve NTM surveys so that the mechanisms for the global spread of MAC disease will become clearer in the near future. Better understanding of the niches exploited by MAC and its ecology is essential for preventing MAC infections and developing new methods for its effective treatment and elimination.